Indigenous biography and autobiography - Read, Peter, 1945-; Peters-Little, Frances, 1958-; Haebich, Anna (Aboriginal history monograph series, 2008)
"In this absorbing collection of papers Aboriginal, Maori, Dalit and western scholars discuss and analyse the difficulties they have faced in writing Indigenous biographies and autobiographies. The issues range from balancing the demands of western and non-western scholarship, through writing about a family that refuses to acknowledge its identity, to considering a community demand not to write anything at all. The collection also presents some state-of-the-art issues in teaching Indigenous Studies based on auto/biography in Austria, Spain and Italy."--Publisher's description